Splintering of tourism market : new appearing forms of cultural tourism as a consequence of changes in everyday lives - Jelinčić, Daniela Angelina (Array, 2009)
Abstract: Within the concept of cultural tourism, this article defines relatively new concepts of creative and hobby tourism, which are detected as recent niche markets. Cultural tourism is a narrow specialized market, while creative and hobby tourism relate to even more specialized segments. Even these specialized forms of tourism have their market whose growth is very probable taking into account changes in everyday work as well as changes in the values of human activity in general. These changes reflect also the sector of tourism, which is obvious in the ever growing splintering of tourism market as well as of tourism forms. The article reviews theoretical concepts of cultural, creative and hobby tourism as to prepare the basis for applied tourist programmes. It looks into the history of cultural tourism as to see what changes occurred and brought it to life. Changes that have taken place in everyday lives of people and the impact of everyday free time activities on tourism are also analysed. Further splintering of the cultural tourism sector is noticed and cultural tourism sub-forms are detected by analysing some of the leading home style and creativity magazines. The article also proposes possible application of push/pull factors to creative/hobby tourism